Bibliometrics and academic staff assessment in Polish university libraries - current trends - Ryś, Danuta; Chadaj, Anna (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
Academic staff assessment in Poland is, to a large extent, based on bibliographic indicators, such as the number of scientific publications produced, the Ministry of Science and Higher Education score pertaining to the journal rank and the publication type, as well as the number of citations and derivatives. Relevant data is retrieved from bibliographic databases developed by libraries, international citation indexes available for Polish scientific institutions under a national licence, and from open-access international and Polish sources, which are briefly presented in the article. The workload entailed, and in consequence, the results of this citation search vary depending on the search method applied. For this reason university staff members and university authorities often seek assistance for this from the university library staff. This in return provides an opportunity for libraries to increase their role within the academic community.In order to investigate the matter further, the authors conducted a survey among the largest academic libraries in Poland. The findings confirm that bibliometric processes (namely, the registration and the formal acceptance of university staff scientific publications, and compilation of citation reports) have become a vital part of modern library work. Bibliographies of university staff publications developed by libraries include various bibliometric indicators (those most frequently used being identified in the article), and have become an important source of statistical and bibliometric information. The survey results highlight the most frequently used bibliometric sources and methods. Examples of bibliographic databases created by the libraries and bibliometric indicators used within these databases are also presented.